EDUKASI KARAKTER “PEDULI LINGKUNGAN” MELALUI PEMANFAATAN BOTOL PLASTIK BEKAS SEBAGAI MEDIA TANAM HIDROPONIK BAGI ANAK USIA DINI - Sunaryanti, Dwi Putri; Ika Puspitasari Dyah Rahmadhani; Tiara Ayu Nugraha Putri; Irzaq Galuh Pranata; Purbowo (BESIRU : Jurnal Pengabdian Masyarakat, 2025)
The low environmental awareness among early childhood students, coupled with the increasing volume of plastic waste, has become an urgent environmental issue. This community service activity aimed to instill environmental care character in early childhood through education on utilizing used plastic bottles as hydroponic planting media at TK Khadijah 1 Nganjuk. The methods included interactive lectures, demonstrations, hands-on practice, and participatory observation-based evaluation. The students were guided to create simple hydroponic planting media using the wick system and hydrogel, utilizing discarded plastic bottles found around the school environment. The results showed an increase in students’ awareness of environmental care, a better understanding of waste recycling, and the creation of environmentally friendly planting media as a solution for plastic waste utilization. This activity proved effective as a character education medium and is replicable for environmental-based early childhood education.